THE PROBLEM OF MODELING ON THE PHYSICS COURCES IN HIGH SCHOOLS - Urazov, Abduxoliq; Eshtuxtarova, Orzigul; Mamasoliyev, Zoir (Физико-технологического образование, 2021)
The article describes the mathematical modeling of physical processes as a method of forming the cognitive activity of students